The Early Modern Invention of Late Antique Rome: How Historiography Helped Create the Crypt of the Popes - Denzey Lewis, Nicola (Archiv für Religionsgeschichte, 2018)
At some point in late antiquity, most scholars believe, Christians reversed the powerful valence of death pollution and considered corpses and bones to be sacred. The rise of the Cult of the Saints' or cult of relics' is widely accepted as a curious social phenomenon that characterized late antiquity. This paper argues that although present elsewhere in the late Roman Empire, no such corporeal turn' happened in Rome. The prevailing assumption that it did - fostered by the apologetic concerns of early modern Catholic historiography - has led us to gloss over important evidence to the contrary, to read our own assumptions into our extant textual, material, and archaeological sources. As a case study', this paper considers the so-called Crypt of the Popes' in the catacombs of Callixtus, which is universally presented unproblematically as an authentic burial chamber attesting to an age of persecution and the strength of Catholic apostolic succession. This paper argues, by contrast, that the chamber is not what it seems; it is, rather, a case of early modern historiographical artifice masquerading as late antique Roman Christianity.